CONTROL NODAL VOLTAGE LOSSES OF ELECTRIC POWER SYSTEM WITH CORRECTION TRANSFORMATION RATIOS - Аракелян, Варужан (SWorldJournal, 2024)
Introductory speech on the research topic: Electrical systems are complex systems. Multifaceted connections between the elements of modern electrical systems determine the features of their management. In the course of research, the system is modeled by